Contemporary challenges in social science management skills gaps and shortages in the labour market - Grima, Simon; Özen, Ercan; Sood, Kiran; Thake, Anne Marie (Emerald Publishing Limited, 2024)
The digital revolution and automation are accelerating changes in the labour market and in workplace skills. Affected by changes in international economics and opportunities for employment, in the workplace individuals seek to acquire relevant skills and retain transferable skills to be employable and to remain in employment. Contemporary Challenges in Social Science and Management Part A and B explore in detail the theoretical competency framework to address these gaps and shortages in different disciplines and sectors. The global drivers of change are analysed and the opportunities and challenges for skills development are investigated, include the transition from education to employment in knowledge-based sectors in different countries. Enriched and strengthened with European case studies of real-life situations providing a practical and industry insights, the volumes collate experts in Economics, Finance, Public Policy, Human Resources, and Risk management, contributing on employability, labour markets, sustainability, and skills of the future from across the globe. Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance. Both disciplinary and interdisciplinary studies are welcome.
Includes index.